Efficacy and safety of radiofrequency ablation for hepatocellular carcinoma in the caudate lobe of the liver. Issue 5 (17th October 2012) - Nishigaki, Youichi; Tomita, Eiichi; Hayashi, Hideki; Suzuki, Yusuke; Iritani, Soichi; Kato, Tomohiro; Yamada, Tetsuya
<x xml:space="preserve">Abstract</x> Aim Radiofrequency ablation (RFA) is a promising alternative to hepatic resection for the treatment of hepatocellular carcinoma (HCC) located in the caudate lobe. We evaluated the therapeutic efficacy and safety of RFA for HCC located in the caudate lobe compared with HCC located elsewhere in the liver. Methods Overall, 555 consecutive patients treated by RFA for a single HCC tumor of less than 3 cm diameter, were enrolled in this study, including 20 patients with HCC located in the caudate lobe. Among these 20 patients, HCC was located in the Spiegel lobe in eight patients, in the paracaval portion in another 10 and in the caudate process in two. We evaluated differences in the local recurrence rate and the incidence of complications associated with RFA between the caudate and the non‐caudate groups. Results The 4‐year cumulative local recurrence rate after RFA in the caudate group and the non‐caudate group was 22.3% and 4.5%, respectively (P < 0.001). Multivariate analysis of factors affecting local recurrence demonstrated that tumor size and tumor location (caudate or non‐caudate) were independent significant factors. No postoperative complications were observed in the caudate group, whereas 15 patients (2.8%) in the non‐caudate group experienced complications related to RFA. Conclusion We were able to safely treat HCC located in the caudate lobe by RFA. However, there was a high incidence of local recurrence, presumably because of the heat sink effect of the inferior vena cava and the restricted puncture approach. We should pursue a revised method to reduce local recurrence.